2007
DOI: 10.1002/star.200600598
|View full text |Cite
|
Sign up to set email alerts
|

Modified Corn Starches with Improved Comprehensive Properties for Preparing Thermoplastics

Abstract: A novel method of starch modification was developed to obtain thermoplastic starch plastics with improved comprehensive properties. Corn starch was oxidized under mild conditions using sodium periodate to prepare dialdehyde starch, which had an acceptable average molecular weight. The dialdehyde starch with 35.2% carbonyl content was reacted with different alcohols (methanol, ethanol, and glycol) to prepare a series of novel starch derivatives, whose structures were characterized by 1H‐NMR and FT‐IR. The therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 45 publications
5
61
0
2
Order By: Relevance
“…Nevertheless, the characteristic absorption peak around 1740 cm -1 , corresponding to carbonyl (C=O) stretching vibration, presented a very weak intensity due to the formation of hemiacetal linkage between oxidised and non-oxidised starch residues (Zhang et al, 2007;Zhang et al, 2014). It is remarkable that the absorption peaks in samples with oxidised starch decreased in intensity at a constant wavenumber, as previously described by other authors (Rivero et al (2010) for crosslinked polymer structures, probably associated with the major restrictions for bond vibration.…”
Section: Atr Ftir Analysissupporting
confidence: 58%
See 2 more Smart Citations
“…Nevertheless, the characteristic absorption peak around 1740 cm -1 , corresponding to carbonyl (C=O) stretching vibration, presented a very weak intensity due to the formation of hemiacetal linkage between oxidised and non-oxidised starch residues (Zhang et al, 2007;Zhang et al, 2014). It is remarkable that the absorption peaks in samples with oxidised starch decreased in intensity at a constant wavenumber, as previously described by other authors (Rivero et al (2010) for crosslinked polymer structures, probably associated with the major restrictions for bond vibration.…”
Section: Atr Ftir Analysissupporting
confidence: 58%
“…The thermoprocessing of these films implies the application of high temperatures, which could extend the interaction between both DAS and proteins, increasing film browning. In addition, the formation of carbonyl groups decreases the thermal stability of DAS Zhang et al, 2007), limiting its application in thermoprocessing methods.…”
Section: Starch-protein Blend Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra show an intense band at 1637 cm-1, which was assigned to deformation vibrations of water molecules absorbed by starch [12]. The broad band at 1735 cm-1 is characteristic of C=O groups (stretching vibration), produced by oxidation of hydroxyl groups to aldehyde and carboxyl groups [13]. FT-IR spectra of oxidized starch prepared with H2O2 ( Figure 1, Curve (a)) exhibited a higher intensity of this absorption peak than other starches (curve (b, c, d)) correlating with its higher carbonyl content as measured by titration (see Table. 1).…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…In previous studies, we found that when the hydroxyl groups in glucose ring of starch were oxidized to aldehyde groups, both the mechanical properties and hydrophobicity of thermoplastic starch were improved [5]. In this study, properties of oxidized starch with carboxyl of same content by Hydrogen Peroxide, Chlorine Dioxide and Sodium Hypochlorite were evaluated, and some properties of them were investigated.…”
Section: Introductionmentioning
confidence: 96%